Efeito do uso do solo na qualidade do recurso hídrico utilizando análise estatística multivariada - Zanata, Marcelo; Pissarra, Teresa Cristina Tarlé [UNESP]; Ferraudo, Antonio Sergio [UNESP]; Ranzini, Mauricio; Campos, Sergio [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
Changes in soil use in protected areas modify the landscape, and therefore, monitoring water quality in headwaters is essential to improve the population health and control water pollution. The objective of this study was to determine environmental changes as a result of soil use, evaluating physical and chemical characteristics of the water of the drainage network in watersheds. The study was conducted to determine the effects of soil use in watersheds with first order streams, related with management practices of water quality, according to the strategic importance for the supplying source. Watersheds are predominantly covered by sugar cane, reforested with Pinus and native forest. Temperature (TºC), pH, electrical conductivity (EC) and total dissolved solids (TDS) were the parameters determined in the headwaters. Dissolved oxygen (DO) and turbidity (T) were obtained in the lab. The majority of variables and factors were explained by changes in soil use associated with management practices. Two factors resulting from the multivariate analysis showed direct correlation with SDT, CE and pH variables, which shows surface runoff with possible water nitrification of a watershed planted with sugarcane. The second factor showed direct correlation between TCº and T variables, while both were negatively correlated with DO, which shows the seasonality effect on one of the watersheds reforested with Pinus. The results highlight management practices in conservation and maintenance planning of forested areas surrounding headwaters as indicators for higher quality of natural water.
Effect of soil use on the quality of water resource in watershed using multivariate statistical analysis
Keywords: Nitrification; Pinus; Seasonal variation; Sugar cane